Three patients with homozygous familial hypercholesterolemia: Genomic sequencing and kindred analysis. Issue 12 (16th October 2019) - Wong, Karen H.Y.; Levy‐Sakin, Michal; Ma, Walfred; Gonzaludo, Nina; Mak, Angel C.Y.; Vaka, Dedeepya; Poon, Annie; Chu, Catherine; Lao, Richard; Balamir, Melek; Grenville, Zoe; Wong, Nicolas; et al.
Abstract: Background: Homozygous Familial Hypercholesterolemia (HoFH) is an inherited recessive condition associated with extremely high levels of low‐density lipoprotein (LDL) cholesterol in affected individuals. It is usually caused by homozygous or compound heterozygous functional mutations in the LDL receptor ( LDLR ). A number of mutations causing FH have been reported in literature and such genetic heterogeneity presents great challenges for disease diagnosis. Objective: We aim to determine the likely genetic defects responsible for three cases of pediatric HoFH in two kindreds. Methods: We applied whole exome sequencing (WES) on the two probands to determine the likely functional variants among candidate FH genes. We additionally applied 10x Genomics (10xG) Linked‐Reads whole genome sequencing (WGS) on one of the kindreds to identify potentially deleterious structural variants (SVs) underlying HoFH. A PCR‐based screening assay was also established to detect the LDLR structural variant in a cohort of 641 patients with elevated LDL. Results: In the Caucasian kindred, the FH homozygosity can be attributed to two compound heterozygous LDLR damaging variants, an exon 12 p.G592E missense mutation and a novel 3kb exon 1 deletion. By analyzing the 10xG phased data, we ascertained that this deletion allele was most likely to have originated from a Russian ancestor. In the Mexican kindred, the strikingly elevated LDL cholesterol level can be attributed to a homozygous frameshift LDLR variant p.E113fs. Conclusions: While the application of WES can provide a cost‐effective way of identifying the genetic causes of FH, it often lacks sensitivity for detecting structural variants. Our finding of the LDLR exon 1 deletion highlights the broader utility of Linked‐Read WGS in detecting SVs in the clinical setting, especially when HoFH patients remain undiagnosed after WES. Abstract : The genetic defects underlying homozygous familial hypercholesterolemia (HoFH) are difficult to ascertain due to its genetic heterogeneity. Here, we applied whole exome and whole genome sequencing with Linked‐Reads on three HoFH patients and they revealed a deleterious missense mutation, a frameshift mutation, and a novel 3kb deletion, all of which are in the LDLR gene. Our study underlines the importance of accurate structural variation detection in clinical sequencing pipelines.